Effective replanning and budgetary control systems: Normative characteristics and practical structure - J. G. Kotzé (South African Journal of Business Management, 1984)
The formal management control system exerts a powerful influence over the actions of middle and top level managers in an organization. To ensure that these actions are in the best interests of the organization as a whole, careful thought should be given to the design of such a control system. The design should incorporate certain desirable characteristics. These characteristics are identified, described and listed in the format of a normative model. A practical management control system which has been implemented in several organizations is subsequently discussed and evaluated against the requirements of the normative model.
Keywords: 650